Pengembangan Kemandirian Pengurus Musholla SMA Negeri 1 Jakenan Pati melalui Pelatihan Instalasi Audio - Ahmad, Fahrudin; Supari, Supari; Margiantono, Agus; Pinandita, Satria (Jurnal Pengabdian KOLABORATIF, 2026)
Sub-optimal management of musholla audio systems is often caused by limited technical competence among administrators and the absence of structured standard operating procedures (SOPs). This Community Service program aimed to enhance the self-reliance of musholla administrators at SMA Negeri 1 Jakenan Pati through practice-based training in audio installation and maintenance. The implementation methods included needs-assessment surveys, technical planning, hands-on training, pre- and post-test evaluations, and the development of SOPs for installation, troubleshooting, and periodic maintenance. A total of 20 participants, consisting of musholla administrators and school technical staff, took part in the program. Evaluation results showed an improvement in scores from a range of 40–70 in the pre-test to 62–95 in the post-test. In addition, the quality of the audio installation improved through cable reorganization, signal level adjustment, and equalizer tuning according to room characteristics. The program also produced practical outputs in the form of training modules and operational SOPs. Overall, the results indicate that practice-based training is effective in enhancing technical competence while simultaneously fostering partner self-reliance in managing musholla audio systems.